EFEKTIVITAS PENGGUNAAN KOMBINASI MODEL PBL, NHT, DAN TGT DIBANTU PERMAINAN ENGKLEK DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PADA PEMBELAJARAN IPAS KELAS IV SD - Chairunnisa Wulandari; Zain Ahmad Fauzi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problem addressed in this research is the low level of students' critical thinking skills This is caused by a one-way, monotonous learning process with minimal variation in activities. The implemented solution is a combination of PBL, NHT, and TGT models assisted by the traditional game Engklek. This study aims to analyze students' critical thinking skills. The research uses Classroom Action Research, conducted over three meetings. The subjects of the study are fourth-grade students. The data collected is qualitative, obtained through observation of students’ critical thinking skills. The results show a consistent improvement from the first to the third meeting. At the first meeting, students’ critical thinking skills were categorized as “Almost All Not Very Skilled,” increasing to “A Few Very Skilled” at the second, and “Almost All Very Skilled” at the third meeting. The implementation of the combined learning models effectively enhanced students' critical thinking skills in each session.